2006
DOI: 10.1598/jaal.49.5.4
|View full text |Cite
|
Sign up to set email alerts
|

“Real‐World Cognition Doesn't End When the Bell Rings”: Literacy Instruction Strategies Derived From Situated Cognition Research

Abstract: This article discusses situated cognition research and its impact on literacy studies concepts and instruction. It provides a brief historical comparison of cognitive psychology and situated cognition and emphasizes the importance of understanding the complex relationships that exist between learners, the settings in which they engage in cognitive activities, and the reconceptualization of time and its usage. Two classroom strategies derived from the work of Jean Lave and Sylvia Scribner are discussed in depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Situated cognition is a complex interplay between physical and social context, authenticity of experience, and personal construction of knowledge (Darvin, 2006;Hendricks, 2001). …”
Section: Situated Cognitionmentioning
confidence: 99%
“…Situated cognition is a complex interplay between physical and social context, authenticity of experience, and personal construction of knowledge (Darvin, 2006;Hendricks, 2001). …”
Section: Situated Cognitionmentioning
confidence: 99%
“…Rachal () noted that “adult education, even more so than childhood and adolescent education, has a direct and symbolic relationship with the environment in which it occurs” (p. 3). Darvin () suggested that it is critical when working with older learners who are reluctant readers and writers to situate instruction within authentic contexts that the learner chooses. Thus, it seems particularly important that adults with extensive support needs should receive literacy instruction that is clearly linked to their interests and everyday lives.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…Instruction for adults must consider their typically pragmatic, problem‐centered orientation to learning (Darvin, ). Motivation, self‐direction, and task/learning organization all seem to play important roles in the experiences of most adult learners, depending on the context and the individual's background and learning characteristics (Merriam, ).…”
mentioning
confidence: 99%
“…A number of researchers acknowledge that online facilitation behavior is generated by a cognitive activity at the same time that it generates this activity (Darvin, 2006). This point of view stresses the impact of both cognitive activity and context variables on online facilitation behavior, and therefore, the situated nature of online facilitation (Darvin, 2006;Lave & Wenger, 1991).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This point of view stresses the impact of both cognitive activity and context variables on online facilitation behavior, and therefore, the situated nature of online facilitation (Darvin, 2006;Lave & Wenger, 1991). Within the broad area of research on peer tutoring little empirical evidence is found in view of gaining insight into tutors" cognitive activity when facilitating younger peers" collaborative learning.…”
Section: Theoretical Backgroundmentioning
confidence: 99%